Textbook of Contact Dermatitis - Rycroft, Richard J. G.; Menné, Torkil; Frosch, Peter J.; Benezra, Claude (Springer Berlin Heidelberg, 1992)
Ideally every patient with eczema should be patch tested and the importance of this investigation is now universally accepted. The simplicity of the technique belies its many pitfalls, the greatest being to lack the knowledge required to select the correct allergens and to interpret the results. The introduction, nearly 20 years ago, of the journal Contact Dermatitis greatly stimulated the reporting of the clinical side of contact dermatitis but a vast amount of laboratory work has also been published in other journals on the mechanisms and theory of these reactions. The literature on the subject is now quite vast and a comprehensive book on the clinical and research aspects of contact dermatitis has been sorely needed. This textbook was carefully planned to gather together what is known of the subject into a cohesive whole and it has succeeded admirably. It consists of 22 chapters written by 41 contributors, each selected for their special study of particular subjects. Every feature of contact dermatitis has been covered, beginning with its history and even concluding with the names and addresses of those worldwide who have a specific interest in the subject. The text is illustrated and well laid out; it has been broken up into clearly demarcated sections making it easy to read and its information readily accessible. One's own writing concentrates the mind but editing the texts of authors from so many different countries was a task of considerable proportions